Cyberspace: multiple times, new worldviews - Barros, Ana Taís Martins Portanova (2008)
The modern physics destroyed the medieval view of space, which distinguished one place for matter and another for the spirit, showing that all space is material. Nowadays, the technology brought the cyberspace that, in its immateriality, can welcome the spirit. Both celebrating and execrating cyberspace indicate the attribution of an ontological character to it, and an imaginary that polarizes itself into homogenizing tendencies of transcendence and immanence.